PENYUSUNAN PERENCANAAN PEMBANGUNAN DI KAMPUNG MENGKAPAN KECAMATAN SUNGAI APIT KABUPATEN SIAK TAHUN 2016-2017 - Mardianti, Yuni; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the preparation of village development planning which is very important for the community in determining future development. In its development planning it is of inferior quality because it experiences constraints such as community participation is not maximal and does not favor the community. The presence of Musrenbang participants who were dominated by the village government and the ineffective development proposal from the number of Musrenbang participants. So that the formulation of the problem in this study is, why is the quality of planning and development of Mittings Village in Sungai Apit Sub-District of Siak in 2016-2017 less optimal. In addition, this study aims to describe the preparation of village development plans and find out which development priorities are less effective. The method used in this study is a descriptive approach to the type of qualitative research. This type of research data is primary data and secondary data. The data collection technique used is qualitative descriptive data analysis technique.The results showed that the quality of village development planning preparation was still not good. This can be seen from a number of data obtained from the village of Mittings, sub-districts and field data collected. The right solution to overcome this problem is the need for support from the village government in increasing community participation in the form of socialization and direct involvement in the field and there needs to be an understanding in the form of motivation to the community to be more active in issuing opinions or proposals for development that are in line with the hopes and needs of the community . Keywords: Planning Principles, Participation, Musrenbang.